Practical Applications in Building a Proposed Program for Islamic Education - Altai , Taiba Zidan Khalaf; Hadithi, Ihsan Omar Mohamed (Journal of Ecohumanism, 2024)
The problem of the current research lies in the importance of the program in the educational process and the importance of the Islamic education subject, which is intended to studyIssuesandChallengesthatI was busyMany nations, andfacing our societiesIn contemporary times andNecessaryThe orderIn addressing many contemporary issuesOn the one hand, and also to achieve the desired goals on the other hand, So the problem liesCurrent researchWith the questions (What topics does the program include and what are its components?Suggested program for Islamic education). Hence, the current research aims to: (identify topics, build a program in light of those topics), and the current research is defined as (teachers of teaching methods in colleges in Baghdad), and to achieve the research objectives, the researchers adopted a set of procedures that included identifying the research sample from its community, which numbered (110), and the total sample was (60) chosen randomly and this sample constituted (10%) of the research community, and the researchers used the questionnaire as a tool for their research after verifying its validity and reliability, and the data was processed statistically, and the result that the researchers reached was that the topics included in the research tool had all received the approval of the research sample, and in light of that, those topics became the basis for building a program for the subject of Islamic education for the primary stage, and in light of those results, the researchers reached a number of numerous recommendations and proposals.